Formulation and evaluation of mouth dissolving tablets of carvedilol - Himmat Singh; Swatantra Ku. Mishra; Rakesh Varma; Sandeep Singh Parihar (International Journal of Pharma and Bio Sciences, 2011)
The aim of the present research work was to enhance the solubility of Carvedilol by solid dispersion method and to formulate a mouth dissolving tablet. Drugs are more frequently taken by oral administration. The solubility of Carvedilol enhanced with different ratios of PVP by the solvent evaporation method .In-vitro release profile of solid dispersion obtained in SGF with out enzymes and Ph 6.8 phosphate buffer indicate that 100% drug release found within 20 min. These solid dispersion were directly compressed into tablets using crospovidone, sodium starch glycol ate, croscarmellose sodium and polacrilin potassium in different concentrations as a superdisintgrants. The prepared tablets containing the solid dispersion of Carvedilol having sufficient strength of 2.5-4 kg/cm2. The disintegranted in the oral cavity with in 21 sec. contain crospovidone (5%) as super disintegrant.